2018
DOI: 10.1186/s12931-017-0698-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Mas-related G Protein coupled receptor X2 in asthmatic lung mast cells and its activation by the novel neuropeptide hemokinin-1

Abstract: Hemokinin-1 (HK-1) is a novel neuropeptide produced by human bronchial cells and macrophages and causes contraction of human bronchi ex vivo. It is also generated by antigen/IgE-activated murine mast cells (MCs) and contributes to experimental chronic allergic airway inflammation via the activation of the neurokinin receptor-1 (NK-1R) expressed on murine MCs. We found elevated MC numbers in the lungs of individuals who died from asthma (asthma) when compared to lungs of individuals who died from other causes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 16 publications
3
149
0
Order By: Relevance
“…Similarly, MRGPRX2 protein expression declined in vitro, but was still measurable in the majority of cases (Figure B). To assess whether reduced MRGPRX2 expression translates to functional impairment, we measured MC degranulation responses to the prototypical MGPRX2‐ligand c48/80 and found that histamine release was indeed depressed in cultured MCs, yet responses were still detectable (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, MRGPRX2 protein expression declined in vitro, but was still measurable in the majority of cases (Figure B). To assess whether reduced MRGPRX2 expression translates to functional impairment, we measured MC degranulation responses to the prototypical MGPRX2‐ligand c48/80 and found that histamine release was indeed depressed in cultured MCs, yet responses were still detectable (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…While allergic MC activation proceeds via a three component system of high affinity IgE receptor (FcεRI), allergen‐specific IgE and the matching allergen, the clinically undistinguishable pseudo‐allergic reaction requires only two components, the receptor MRGPRX2 and one of its numerous ligands, for example compound 48/80 (c48/80), Substance P (SP), other neuropeptides or drugs . Contrary to FcεRI, MRGPRX2 is mostly confined to MC TC type MCs (MCs in skin), and skin MCs were the only samples to express MRGPRX2 across the FANTOM5 atlas . MCs used for research purposes are typically expanded in culture, and this provides a different microenvironment compared to the cells’ natural habitat, inducing adaptations in the MCs .…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell MRGPRX2 plays a pivotal role in mediating pseudo-allergic reactions to several FDA approved drugs (3,(19)(20)(21)(22)(23)(24) and chronic inflammation associated with asthma (18), urticaria (7), and rosacea (6). We have identified a role for SOCE via STIM1 in regulating MRGPRX2 responses in mast cells.…”
Section: Discussionmentioning
confidence: 96%
“…LL-37 expression is upregulated in patients with chronic inflammatory skin conditions such as rosacea (17), suggesting that mast cell activation via MRGPRX2 may be responsible for the symptoms associated with this disease. In addition, the pathology of several allergic diseases such as asthma (18) and urticaria (7) correlate with mast cell-specific expression of MRGPRX2. Mouse mast cells express MrgprB2, an ortholog of the human receptor (3).…”
Section: Introductionmentioning
confidence: 99%
“…Allergic asthma, the most common phenotype of asthma, is clinically de ned by the presence of allergic sensitization and a correlation between asthma symptoms and allergen exposure [18,19]. MrgX2 may promote the development of asthma and may serve as a potential new target for regulating this chronic in ammatory disease [20]. MrgX2 may also be as a potential biomarker for predicting treatment outcomes in allergic asthma [21].…”
Section: Discussionmentioning
confidence: 99%